Epidemiology of the first 100 cases of COVID-19 in Taiwan and its implications on outbreak control (2020)
Purpose: To describe the epidemiology and outcome of the first 100 COVID-19 cases in Taiwan. Methods: We included the first 100 patients with laboratory-confirmed SARS-CoV-2 infection in Taiwan. Demographic, clinical, epidemiological and laboratory data were extracted from outbreak investigation reports and medical records. Results: Illness onset of the 100 patients was during January 11 to March 16, 2020. Twenty-nine (29%) had at least one underlying condition and ten (10%) were asymptomatic. Seventy-one were imported, including four clusters. Twenty-nine were locally-acquired, including four clusters. The median days from onset to report was longer in locally-acquired cases (10 vs 3 days). Three patients died (case fatality rate 3%) and all of them had underlying conditions. As of May 13, 2020, 93 had been discharged in stable condition; the median hospital stay was 30 days (range, 10e79 days). Conclusion: The first 100 cases of COVID-19 in Taiwan showed the persistent threat of imported cases from different countries. Even though sporadic locally-acquired disease has been identified, through contact investigation, isolation, quarantine and implementation of social distancing measures, the epidemic is contained to a manageable level with minimal local transmission.